2014
DOI: 10.1177/0022034514564186
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenins as Potential Buffers during Secretory-stage Amelogenesis

Abstract: Amelogenins are the most abundant protein species in forming dental enamel, taken to regulate crystal shape and crystal growth. Unprotonated amelogenins can bind protons, suggesting that amelogenins could regulate the pH in enamel in situ. We hypothesized that without amelogenins the enamel would acidify unless ameloblasts were buffered by alternative ways. To investigate this, we measured the mineral and chloride content in incisor enamel of amelogenin-knockout (AmelX -/-) mice and determined the pH of enamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
1
24
0
2
Order By: Relevance
“…Amelogenins can bind to as many as 10–14 protons per molecule in vitro and could potentially serve as a buffer. A buffering role for amelogenins in situ corroborates with the finding that in amelogenin‐deficient ( Amelx‐ null) mice, formation of minerals in enamel is not reduced but initially even accelerated . In addition, immunohistochemistry showed that secretory ameloblasts in Amelx‐ null mice prematurely expressed AE2a,b protein, suggesting that bicarbonate buffering compensates for the absence of buffering by amelogenins .…”
supporting
confidence: 79%
“…Amelogenins can bind to as many as 10–14 protons per molecule in vitro and could potentially serve as a buffer. A buffering role for amelogenins in situ corroborates with the finding that in amelogenin‐deficient ( Amelx‐ null) mice, formation of minerals in enamel is not reduced but initially even accelerated . In addition, immunohistochemistry showed that secretory ameloblasts in Amelx‐ null mice prematurely expressed AE2a,b protein, suggesting that bicarbonate buffering compensates for the absence of buffering by amelogenins .…”
supporting
confidence: 79%
“…This local hypermineralization in the enamel matrix depletes the local reservoir or free calcium ions and then may also act as a physical barrier, impairing diffusion of ions and peptides, to result in a subsequent band of hypomineralized enamel (Guo et al 2015 ). Therefore, within the matrix, it is possible that a more rapid mineral precipitation in the presence of fl uoride may result in the presence of hypermineralized bands followed by hypomineralized bands in the enamel matrix (Bronckers et al 2009 (Guo et al 2015 ).…”
Section: Fluoride Exposure Causes Both Hyper-and Hypomineralization Omentioning
confidence: 99%
“…Protons generated during HAP formation in the maturation stage are neutralized by bicarbonate secreted from the apical end of ruffl ed-ended maturation ameloblasts through anion exchangers of the Slc26a family (Jalali et al 2014 ). Transmembrane proteins, including cystic fi brosis transmembrane conductance regulator, anion exchanger-2, carbonic anhydrase-2, and sodium hydrogen exchanger-1, are involved in this pH regulation mechanism (Guo et al 2015 ;Lyaruu et al 2008 ;Alper 2009 ;Concepcion et al 2013 ). In the fl uorosed enamel matrix, retention of amelogenin protein may also buffer pH changes in the matrix, secondary to mineral formation, thereby reducing the acidification of the matrix under ruffl e-ended ameloblasts (Guo et al 2015 ).…”
Section: Fluoride Exposure Causes Both Hyper-and Hypomineralization Omentioning
confidence: 99%
“…This local hypermineralization in the enamel matrix depletes the local reservoir or free calcium ions and then may also act as a physical barrier, impairing diffusion of ions and peptides, to result in a subsequent band of hypomineralized enamel (Guo et al 2015 ). This local hypermineralization in the enamel matrix depletes the local reservoir or free calcium ions and then may also act as a physical barrier, impairing diffusion of ions and peptides, to result in a subsequent band of hypomineralized enamel (Guo et al 2015 ).…”
Section: Fluoride Exposure Causes Both Hyper-and Hypomineralization Omentioning
confidence: 99%
“…In the presence of fluoride, increased mineral formation may result in local acidification, which is buffered by amelogenin proteins in the enamel matrix at the secretory stage (Guo et al 2015 ). Therefore, regulation of matrix pH by ameloblasts is crucial for sustained crystal growth.…”
Section: Fluoride Exposure Causes Both Hyper-and Hypomineralization Omentioning
confidence: 99%